Differential transcription of baculovirus late and very late promoters: fractionation of nuclear extracts by phosphocellulose chromatography. - Xu, B (1995)
An in vitro transcription system based on cytidine-free cassette was developed for the late 39k gene and the very late polyhedrin gene of Autographa californica nuclear polyhedrosis virus (AcNPV). Optimization of transcription conditions revealed that a preincubation step was not required for transcription of late and very late promoters, although preincubation was essential for efficient transcription from an early promoter. The 39k and polyhedrin constructs were actively transcribed by nuclear extracts prepared from AcNPV-infected Spodoptera frugiperda cells at 12 or 36 h postinfection but not by nuclear extracts prepared from uninfected or infected cells harvested during the early phase of infection. Transcription from the very late polyhedrin promoter was fivefold higher than that from the 39k late promoter with the nuclear extract prepared at 36 h postinfection. The 36-h extract was fractionated by phosphocellulose chromatography. Transcription activity eluted in two fractions, at 0.3 and 0.5 M KCl. Both the 39k and polyhedrin constructs were transcribed by these fractions; however, the patterns of late and very late transcription were distinctly different. With the 0.3 M fraction, incorporation into the 39k transcript was approximately 10-fold higher than incorporation into the polyhedrin transcript. Alternatively, with the 0.5 M fraction, transcription of the polyhedrin construct was twofold higher than transcription of the 39k construct. These results indicate that this in vitro system will be useful for purification and identification of factors that discriminate between late and very late promoters.